PERENCANAAN STRATEGIS DAN RENCANA PENGEMBANGAN SEKOLAH (RPS/RKS) UPT SD NEGERI 9 TAMALATEA - Ainun Taswira; Suardi; Idawati (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study aims to analyze the process of strategic planning and the implementation of the School Development Plan (RPS/RKS) as a strategic management instrument in UPT SD Negeri 9 Tamalatea. The research was conducted using a descriptive qualitative approach to obtain an in-depth understanding of the planning process, stakeholder involvement, and the effectiveness of program implementation. Data were collected through interviews with the principal, teachers, and the school committee, complemented by observations, document analysis, and questionnaires. The results show that the RPS/RKS document has been well structured, aligning the school’s vision, mission, and goals with national education policies. However, the level of teacher participation in the planning process remains limited, and program implementation has not fully reflected the plans outlined in the document. Monitoring and evaluation activities are still conducted administratively without systematic performance indicators. The study concludes that the effectiveness of school strategic planning depends largely on participatory processes, managerial capacity, and continuous evaluation. Therefore, schools need to strengthen teacher involvement and establish a data-based evaluation system to ensure that the RPS/RKS serves as a dynamic tool for improving educational quality rather than merely fulfilling administrative requirements.